3D Bioprinted GelMA‐Nanoclay Hydrogels Induce Colorectal Cancer Stem Cells Through Activating Wnt/β‐Catenin Signaling. Issue 18 (1st March 2022) - Zhang, Yanmei; Wang, Zixuan; Hu, Qifan; Luo, Hao; Lu, Bingchuan; Gao, Yunhe; Qiao, Zhi; Zhou, Yongsen; Fang, Yongcong; Gu, Jin; Zhang, Ting; Xiong, Zhuo
Abstract: Cancer stem cells (CSCs) are a rare cell population in tumors that are responsible for tumor recurrence and metastasis. They are a priority as therapeutic targets, however, assays targeting CSCs have been limited by expanding and maintaining CSCs in vitro. Here, the authors find that gelatin methacryloyl (GelMA)‐nanoclay hybrid hydrogels can induce and enrich colorectal CSCs assisted by three‐dimensional (3D) bioprinting. The presence of the nanoclay increases the printability, Young's modulus, pore size, and cytocompatibility of the hydrogels. Bioprinted GelMA‐nanoclay hydrogels promote the formation of spheroids expressing elevated levels of the stemness markers LGR5, CD133, CD26, and SOX2. Cancer cells grown in GelMA‐nanoclay hydrogel possess higher self‐renewal and differentiation capacity in vitro and higher tumorigenic capacity in vivo. GelMA‐nanoclay hydrogels induce CSCs by stimulating the activation of the Wnt/β‐catenin signaling pathway. Further studies demonstrate that spheroids from GelMA‐nanoclay hydrogels possess increased stemness, higher consistency, yield, and sensitivity to the anti‐CSC compounds compared to the classic CSC‐enrichment model. Collectively, this study may provide a valuable biomaterial and method for inducing and enriching CSCs, to facilitate the effective CSC‐targeting drug screening. Abstract : This paper reports that 3D bioprinted gelatin methacryloyl (GelMA)‐nanoclay hybrid hydrogels can induce and enrich colorectal cancer stem cells (CSCs) by promoting the formation of spheroids through activating Wnt/β‐catenin signaling. These spheroids can be isolated easily from the hydrogels and are promising CSC enrichment models with increased stemness, high consistency, yield, and efficiency for CSC‐targeting drug screening.